2021
DOI: 10.1038/s41467-021-22964-w
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic peptides exhibit antiviral effects against influenza virus HA and prevent pneumonia in animal models

Abstract: Most anti-influenza drugs currently used, such as oseltamivir and zanamivir, inhibit the enzymatic activity of neuraminidase. However, neuraminidase inhibitor-resistant viruses have already been identified from various influenza virus isolates. Here, we report the development of a class of macrocyclic peptides that bind the influenza viral envelope protein hemagglutinin, named iHA. Of 28 iHAs examined, iHA-24 and iHA-100 have inhibitory effects on the in vitro replication of a wide range of Group 1 influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…A more recent study identified potent teMP ligands against influenza hemagglutinin and demonstrated that the peptides inhibited in vitro replication of a broad range of group 1 influenza viruses. 2 One of the teMPs (iHA-100), a 15-mer macrocycle bearing four N-methylated amino acids, exhibited high efficacy in inhibiting the growth of highly pathogenic influenza viruses and preventing severe pneumonia at later stages of infection in mouse and non-human primate cynomolgus macaque models (Figure 4c). These case studies illustrate high therapeutic potential of teMPs in vivo.…”
Section: Potential Of the Thioether-closed Macrocyclic Peptides Obtai...mentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study identified potent teMP ligands against influenza hemagglutinin and demonstrated that the peptides inhibited in vitro replication of a broad range of group 1 influenza viruses. 2 One of the teMPs (iHA-100), a 15-mer macrocycle bearing four N-methylated amino acids, exhibited high efficacy in inhibiting the growth of highly pathogenic influenza viruses and preventing severe pneumonia at later stages of infection in mouse and non-human primate cynomolgus macaque models (Figure 4c). These case studies illustrate high therapeutic potential of teMPs in vivo.…”
Section: Potential Of the Thioether-closed Macrocyclic Peptides Obtai...mentioning
confidence: 99%
“…Q. M.KawaokaY.OgasawaraK.Tsukiyama-KoharaK.SugaH.KoharaM. Saito, M. Itoh, Y. Yasui, F. Munakata, T. Yamane, D. Ozawa, M. Ito, R. Katoh, T. Ishigaki, H. Nakayama, M. Shichinohe, S. Yamaji, K. Yamamoto, N. Ikejiri, A. Honda, T. Sanada, T. Sakoda, Y. Kida, H. Le, T. Q. M. Kawaoka, Y. Ogasawara, K. Tsukiyama-Kohara, K. Suga, H. Kohara, M. Nat. Commun.2021122654 …”
Section: Key Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This system helps in the identification of high-affinity ligands for a protein of interest. Using the RaPID system, Saito et al [66] obtained macrocycles named iHAs that can bind influenza HA. Among these peptides, iHA-100 inhibits both viral adsorption (IC 50 = 0.036 µM) and membrane fusion (EC 50 = 0.07 µM) by interacting with the HA stalk domain.…”
Section: The Peptide Iha-100 Generated By a Macrocyclic Peptide Expre...mentioning
confidence: 99%
“…The peptides were synthesized by Cellmano Biotech Limited (Hefei, Anhui, China). All peptides were assembled on Peptide Synthesizer SyroI (Biotage, Uppsala, Sweden) using the standard solid-phase peptide synthesis method as previously described [25,26]. The peptides were aliquot and stored in −80 • C until use.…”
Section: Virus Cell Lines and Peptidesmentioning
confidence: 99%